Balancing the Risk of Cardiotoxicity Outcomes in Treatment Selection for Multiple Myeloma: A Retrospective Multicenter Evaluation of Ixazomib, Lenalidomide, and Dexamethasone (IRd) Versus Carfilzomib, Lenalidomide, and Dexamethasone (KRd) - Benjamin J. Lee; Michael Sayer; Ali A. Naqvi; Karen T. Mai; Pranav M. Patel; Lisa X. Lee; Aya F. Ozaki (eJHaem)
ABSTRACT Introduction Carfilzomib use has been extensively associated with cardiovascular toxicity; the risk with ixazomib, a novel oral proteasome inhibitor, is underreported and no large comparative analysis is available. Methods We conducted a retrospective cohort study utilizing the TriNetX platform to compare toxicity outcomes among multiple myeloma patients who received lenalidomide, dexamethasone, and ixazomib (IRd) or carfilzomib (KRd). Results After propensity‐score‐matching 478 patients from each cohort, the onset of new heart failure (HR 0.25; p < 0.001) and arrhythmias (HR 0.57; p = 0.014) at 6 months were significantly lower with IRd while overall survival at 3 years was similar (p = 0.50). Conclusion IRd is associated with a significantly lower risk of cardiac toxicities compared to KRd.